Study on the biomechanical properties of 3D printed blended esophageal stents with different structural parameters based on patient CT - Wu, Guilin; Wei, Guihong; Huang, Shenghua; Zhang, Qilin; Zeng, Shuai; Feng, Jun; Zeng, Bo; Yu, Peng (Frontiers in Physics, 2024)
Introduction: Esophageal stenting is a widely used treatment for esophageal diseases, which can also be used for adjuvant therapy and feeding after chemotherapy for esophageal cancer. The structural parameters of the stent have a significant impact on its mechanical properties and patient comfort. Methods: In the present work, we reconstructed the esophagus model based on the patient’s computed tomography (CT) data, and designed stents with different structural parameters. We used 3D printing technology to achieve rapid production of the designed stents by using Thermoplastic polyurethane (TPU)/Poly-ε-caprolactone (PCL) blends as the materials. The mechanical properties and effects on the esophagus of polymer stents with four different structural parameters of diameter, wall thickness, length and flaring were investigated by in vitro tests of radial compression and migration of the stents, as well as by finite element simulations of the stent implantation process in the esophagus and of the stent migration process. An artificial neural network model was established to predict the radial force of the stent and the maximum equivalent stress of the esophagus during implantation based on these four structural parameters. Results: The results show that wall thickness was the structural parameter that had the greatest impact on the radial force of the stent (statistically significant, p < 0.01), and flaring was the structural parameter that had the greatest impact on the maximum equivalent stress of the esophageal wall after stent implantation (statistically significant, p < 0.01). No. 6 stent had a maximum radial force of 18.07 N, which exceeded that of commercial esophageal stents and had good mechanical properties. And the maximum equivalent force on the esophagus caused by its implantation was only 30.39 kPa, which can improve patient comfort. The predicted values of the constructed back propagation (BP) neural network model had an error of less than 10% from the true values, and the overall prediction accuracies were both above 97%, which can provide guidance for optimizing the design of the stent and for clinical research. Discussion: 3D printing technology presents a wide range of applications for the rapid fabrication of personalized TPU/PCL blend stents that are more suitable for individual patients.